2008
DOI: 10.5194/bg-5-875-2008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variable air-sea O<sub>2</sub> and CO<sub>2</sub> fluxes on atmospheric potential oxygen (APO) and land-ocean carbon sink partitioning

Abstract: Abstract.A three dimensional, time-evolving field of atmospheric potential oxygen (APO ∼O 2 /N 2 +CO 2 ) was estimated using surface O 2 , N 2 and CO 2 fluxes from the WHOI ocean ecosystem model to force the MATCH atmospheric transport model. Land and fossil carbon fluxes were also run in MATCH and translated into O 2 tracers using assumed O 2 :CO 2 stoichiometries. The modeled seasonal cycles in APO agree well with the observed cycles at 13 global monitoring stations, with agreement helped by including oceani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…This can be done by simulating dAPO cycles using air-sea gas fluxes calculated from an ocean model, using an ATM to transport the fluxes in the atmosphere, and comparing the predicted seasonal cycles in dAPO to observations (Balkanski et al, 1999;Naegler et al, 2007;Nevison et al, 2008;Stephens et al, 1998). Such tests have shown that certain combinations of ocean and atmospheric models can generate dAPO cycles in relatively good agreement with observations.…”
Section: Seasonal Cycles In Apomentioning
confidence: 99%
“…This can be done by simulating dAPO cycles using air-sea gas fluxes calculated from an ocean model, using an ATM to transport the fluxes in the atmosphere, and comparing the predicted seasonal cycles in dAPO to observations (Balkanski et al, 1999;Naegler et al, 2007;Nevison et al, 2008;Stephens et al, 1998). Such tests have shown that certain combinations of ocean and atmospheric models can generate dAPO cycles in relatively good agreement with observations.…”
Section: Seasonal Cycles In Apomentioning
confidence: 99%
“…The model-simulated APO values were derived in accordance with Nevison et al (2008) (2), while X N 2 is the mole fraction of N 2 in the atmosphere and α F is the global average -O 2 :CO 2 exchange ratio for fossil fuel combustion. In this study, we adopted X O 2 = 0.2094, X N 2 = 0.7809 (Tohjima et al, 2005, α F = 1.4 (Keeling and Manning, 2014), and α B have the same meaning as Equation (2).…”
Section: Atmospheric Transport Modelmentioning
confidence: 99%
“…In every study in which APO is simulated by atmospheric transport models driven by estimated oceanic O 2 and CO 2 fluxes, results have shown an equatorial bulge in the annual mean APO (Stephens et al, 1998;Gruber et al, 2001;Naegler et al, 2007;Nevison et al, 2008). Such latitudinal gradient is generally caused by outgassing fluxes of O 2 and CO 2 in the tropical regions and ingassing fluxes in the mid and high latitude regions.…”
Section: Introductionmentioning
confidence: 99%